Pengembangan E-Modul Praktikum Pembuatan Tape Ketan Berbasis Canva untuk Meningkatkan Enterpreneurial Skills dan Kemampuan Kognitif Siswa Madrasah Aliyah - Ina Yuliana; Zaenal Abidin; Asep Ginanjar Arip (Universitas Majalengka, 2023)
The problems of this research are students’ low entrepreneurial skills and cognitive abilities. It can be seen from the results of the pre-research conducted by researcher which showed that there were still students experiencing difficulties in carrying out independent lab-work. Especially X grade students in Natural Science Program who are required to be able to do lab-work, the teacher usually assigns students to do lab-work at home with a guide from a paper module, due to limited time if it is carried out at school. This study aims to find out the effectiveness of using canva based electronic module (E-Modul) lab-work in making tape ketan towards students’ entrepreneurial skills and cognitive abilities. The method used in this research is the Research and Development (R&D) method. This R&D method is used to develop educational products that can be accounted for, namely in the form of a canva based E-Module in making Tape Ketan Lab-work. Based on the result of this research, it shows that the result of the t-test comparing the scores/average scores of the post-test between the two classes (experimental and control groups) is a sig value of less than 0.05 which indicates a significant change. It means that the optimization of test results achieved by students in the experimental group is significantly higher than test result obtained by students in the control group. Based on the result of the research, it can be concluded that the canva based electronic module (E-Modul) in Tape Ketan Lab-work is effective in improving students’ entrepreneurial skills and cognitive abilities. The suggestion in this study is that the teachers should use electronic module in lab-work activities because it is proved that the use of canva based electronic module (E-Modul) in making tape ketan lab-work is effective in improving students’ entrepreneurial skills and cognitive abilities. For the next researchers, it is expected to develop other learning media in order to improve students’ entrepreneurial skills and cognitive abilities.